Measurement of histamine in nasal lavage fluid: Comparison of a glass fiber-based fluorometric method with two radioimmunoassays - Andersson, Morgan; Nolte, Hendrik; Olsson, Martin; Skov, Per Stahl; Pipkorn, Ulf (Journal of allergy and clinical immunology, 1990)
The determination of histamine in nasal secretions and nasal lavage fluid may be of importance to monitor activation of histamine containing cells in the nasal cavity. However, such studies have been besieged by controversy, specifically to findings of changes in histamine levels in relation to allergenic stimulation. This controversy may be due to the specificity and accuracy of the various methods used to determine histamine in the nasal fluid. We have therefore applied and compared three new methods to determine histamine in nasal lavage fluids obtained before and after allergen challenge in normal subjects and patients with allergic rhinitis. We used a fluorometric glass fiber-based histamine method (FHR) and two RIAs, I and II. The FHR (detection limit, 7.0 nmol) and the RIA II (detection limit, 0.2 nmol) are specific for histamine itself, whereas the RIA I (detection limit, 18.0 nmol) measures mainly methylhistamine and cross-reacts to some extent with histamine. The histamine levels in the nasal lavage fluids from the nasal challenges demonstrated histamine values between 100 and 2000 nmol/L of histamine with significantly higher levels in the postallergen challenges for the allergic subjects as compared to the normal control subjects. The FHR correlated well with the RIA I and RIA II methods with correlation coefficients of 0.77 to 0.88 ( p<0.001), respectively. However, the RIA I (methylhistamine antibody) always demonstrated absolute histamine values 5% to 20% of values measured by the RIA II (at the level of cross-reactivity to histamine). This finding indicates that histamine is not rapidly metabolized to methylhistamine on the mucosal surface in contrast to histamine in the circulation. The study demonstrates that the new methods are appropriate for the determination of histamine in nasal secretions, the FHR being less time consuming than the RIA methods.